A FTO variant and risk of acute coronary syndrome - Hubacek, Jaroslav A; Stanek, Vladimír; Gebauerová, Marie; Pilipcincová, Alexandra; Dlouhá, Dana; Poledne, Rudolf; Aschermann, Michal; Skalická, Hana; Matousková, Jana; Kruger, Andreas; Penicka, Martin; Hrabáková, Hana; et al. (Clinica chimica acta; international journal of clinical chemistry, 2010)
BACKGROUND: The FTO gene plays an important role in the determination of body weight and BMI and it has been suspected of being associated with all-case mortality. METHODS: We have analyzed the FTO rs17817449 variant in consecutive 1092 male patients with acute coronary syndrome (ACS) and in 1191 randomly selected Caucasian individuals (population controls). RESULTS: The FTO variant was significantly associated with BMI both in controls (P<0.02) and ACS patients (P<0.01). In both groups, BMI was highest in GG homozygotes and lowest in TT homozygotes. There was a significant difference between the ACS patients and controls in the frequency of the FTO genotype GG (21.4% vs. 15.9%, P<0.005). FTO GG homozygotes had a significantly increased risk of ACS, compared with TT homozygotes which was independent of age and BMI (odds ratio 1.49, 95% confidence interval 1.16-1.93). The odds ratio of ACS patients for the GG genotype remained significant even after the exclusion of diabetics (100 controls and 339 ACS patients), with OR 1.32 (95% CI 1.01-1.72). CONCLUSIONS: This study provides an evidence of an association between the FTO variant and risk of ACS in Caucasian males.
Keywords: Genetic Predisposition to Disease; Male; proteiny; Middle Aged; mužské pohlaví; studie případů a kontrol; genetická variace; gen pro FTO; Genetic Variation; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Humans; lidé středního věku; rizikové faktory; akutní koronární syndrom; genetická predispozice k nemoci; Risk Factors; Proteins; Acute Coronary Syndrome; lidé; Case-Control Studies